2003
DOI: 10.1007/s00432-003-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

Low toxic neoadjuvant cisplatin, 5-fluorouracil and folinic acid in locally advanced gastric cancer yields high R-0 resection rate

Abstract: The presented PLF protocol yields R-0 resection rates comparable to protocols like EAP (etoposide, adriamycin, platinum), but with a better safety profile allowing administration in an outpatient setting. Our study supports PLF as a reference neoadjuvant treatment for gastric cancer even outside of clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Understandably, these studies enrolled only small numbers of patients, but demonstrated a significant benefit for those patients in that about 40% of them were R0 resected after 2 or 3 cycles of systemic chemotherapy [11,12,13,14,15,16]. The Italian group could confirm these results in a larger trial enrolling 82 patients, who were considered not curatively resectable according to laparotomy in 63% and to CT scans in the remaining third.…”
Section: Neoadjuvant Therapy In Patients Not Curatively Resectable Dusupporting
confidence: 66%
“…Understandably, these studies enrolled only small numbers of patients, but demonstrated a significant benefit for those patients in that about 40% of them were R0 resected after 2 or 3 cycles of systemic chemotherapy [11,12,13,14,15,16]. The Italian group could confirm these results in a larger trial enrolling 82 patients, who were considered not curatively resectable according to laparotomy in 63% and to CT scans in the remaining third.…”
Section: Neoadjuvant Therapy In Patients Not Curatively Resectable Dusupporting
confidence: 66%
“…In 6 studies including a total of 264 deWnitely irresectable patients, most of them deWned by laparotomy, R-0-resections were achieved in 14-45% (Wilke et al 1989;Plukker et al 1991;Lerner et al 1992;Cascinu et al 1998;Gallardo-Rincon et al 2000;Cascinu et al 2004). In a study of our group on patients staged either by laparotomy or by endoscopic ultrasound, computed tomography and, in case of conXicting results, surgical laparoscopy, we achieved a 52% R-0-resection rate among 25 patients of stage IIIB and IV M0 (Menges et al 2003) (Table 1).…”
Section: Introductionmentioning
confidence: 74%
“…R-0-resection rates were consistently higher (41-76%) in phase-II-studies including potentially resectable patients (survey in Menges et al 2003).…”
Section: Introductionmentioning
confidence: 92%
“…In 5 studies including a total of 182 definitely irresectable patients, most of them defined by laparotomy, R-0 resections were achieved in 14-44% [4][5][6][7][8]. In a study of our group on patients staged either by laparotomy or by endoscopic ultrasound, computed tomography and, in case of conflicting results, surgical laparoscopy, we achieved a 53% R-0 resection rate among 25 patients of stage III B and IV M0 [9] (table 1). R-0 resection rates were consistently higher (41-76%) in studies including potentially resectable patients (survey in [9]).…”
Section: Efficacy Of the Treatment In Terms Of Achieving R-0 Resectionmentioning
confidence: 98%
“…In a study of our group on patients staged either by laparotomy or by endoscopic ultrasound, computed tomography and, in case of conflicting results, surgical laparoscopy, we achieved a 53% R-0 resection rate among 25 patients of stage III B and IV M0 [9] (table 1). R-0 resection rates were consistently higher (41-76%) in studies including potentially resectable patients (survey in [9]). So far, a benefit of neoadjuvant therapy in potentially resectable patients with gastric cancer has not been demonstrated -recently the first data of a large randomised multicentre trial (the MAGIC-study) were presented: 503 patients with resectable upper gastrointestinal cancer (in 74% gastric cancer), were randomised to receive surgery alone or perioperative chemotherapy (3 pre-and 3 postoperative cycles of ECF: epirubicin (50 mg/m 2 every 3 weeks), cisplatin (60 mg/m 2 every 3 weeks) and infusional 5-fluorouracil (5-FU, 200 mg/m 2 continuously daily).…”
Section: Efficacy Of the Treatment In Terms Of Achieving R-0 Resectionmentioning
confidence: 99%